A Comparative Study of Digital Financial Inclusion in India and China: Challenges and Opportunities for FinTech & UFA by 2020 - Sultana Begum (Eurasian Journal of Management & Social Sciences)
Financial inclusion is a much debated and discussed topic both for inclusive growth and sustainable growth. Both India and China are coming out with various financial reforms and policies to have a sustainable society. In the context of the Indian Financial Inclusion Advisory Committee (FIAC) which is tasked with the preparation of the National Strategy for Financial Inclusion (NSFI) deliberated extensively on its formulation upon international best practices on digital financial inclusion there is a need to explore the opportunities and challenges of using FinTech in India. This paper analytically compares and explores the status quo operandi of India and China on various Financial Inclusion Indicators published by World Bank through the Findex reports. The paper explores the opportunities and Challenges of FinTech in India especially in the context of Digital Financial Inclusion. The findings include that innovative financial service involving use of mobile phones is still in the novice stage in India, there is still a long way to go to remove the gender gap, usage of technology and there is significant variance exists between India and China in the digital financial inclusion indicators. The paper concludes that though there is drastic increase in percentages of most of the indicators of financial inclusion in India from 2014 to 2017, there is still a long way to go to reach the level of China for India. The paper suggests some measures and recommendations for the policy holders to move towards digital financial inclusive society as well as to achieve Universal Financial Access (UFA) by 2020.